Comparison of Negative Affect and Anxiety–Depression Comorbidity among Mothers of Adolescents with Bipolar Disorder, Borderline Personality Disorder, and Healthy Adolescents - Rahimi Kia, Sona; Golabshekar, Masoumeh; Ostadzadeh, Atefeh; Bagherian Sahlavane, Fatemeh; Eslamzadeh, Amirhossein (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare levels of negative affect and anxiety–depression comorbidity among mothers of adolescents with bipolar disorder, borderline personality disorder, and healthy adolescents. Methods and Materials: This cross-sectional, descriptive–comparative study was conducted among mothers in Shiraz between July and September 2023. 58 participants were selected through purposive sampling. Negative affect was assessed using the Positive and Negative Affect Schedule (PANAS), and anxiety, depression, and stress were measured using the Depression Anxiety Stress Scale (DASS-21). Group differences were examined using one-way analysis of variance (ANOVA), with statistical analyses performed in SPSS version 27 at a significance level of 0.05. Findings: No significant differences were observed between mothers of adolescents with bipolar disorder and those with borderline personality disorder in negative affect (p = 0.940) or anxiety (p = 0.584). However, both clinical groups scored significantly higher than mothers of healthy adolescents (p < 0.001). Stress levels differed significantly between the bipolar and borderline groups (p < 0.001), with both groups reporting higher stress compared to mothers of healthy adolescents. Conclusion: The findings suggest that having an adolescent with bipolar or borderline disorder is associated with heightened negative affect, anxiety, and stress among mothers. These results highlight the importance of providing targeted psychological and supportive interventions to promote the well-being of mothers caring for adolescents with severe mental health conditions.